A counter‐narrative of curriculum enrichment in performative times. Issue 4 (12th February 2020) - Livingston, Kay; Doherty, Catherine
Abstract : Political pressures to improve schooling outcomes have typically narrowed the curriculum to that which can be measured. We explore the counter‐narrative of efforts to enrich curriculum with learning, which is difficult to measure but nevertheless valued, through a study of British Council programmes offered in Scottish schools to support curricular internationalisation. These programmes exemplify a growing number of programmes provided by external organisations to enrich official school curriculum. However, the contemporary focus on performative targets means that such hosted programmes need to argue their relevance in terms of measurable curricular outcomes. We draw on an empirical project involving semi‐structured interviews with school leaders and focus groups with teachers in Scottish schools. The research is conceptualised through Bernstein's theory of the classification and framing of knowledge, and distinction between visible and invisible pedagogies. Analysis of two schools' enactment of such curricular enrichment explores how programmes ostensibly cultivating international education and global citizenship are ultimately assessed and defended through their contribution to other curricular outcomes. This counter‐narrative of curricular enrichment in performative times asks whether such efforts to measure the ineffable defeat the object of the exercise, to highlight how overly simplistic measures of curricular learning can distort what matters.